2012
DOI: 10.4314/ijbcs.v5i5.34
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on the flocculation efficiencies of <em>Moringa oleifera</em> (MO), polyacrylamide-grafted gum arabic (GA-g-PAAM) and blended products of MO and PA-g-PAAM

Abstract: Graft copolymerization of polyacrylamide onto gum arabic was carried out in aqueous medium at room temperature (30 o C) using previously optimized concentrations of initiator (ceric ion) and the monomer (acrylamide). The percentage graft yield was high (70%) due to optimization of reaction conditions. Reactive blends of Moringa oleifera (MO) and the graft copolymer (GA-g-PAAM) were also synthesized in different ratios of MO to GAg -PAAM. The blended and unblended graft copolymers and Moringa oleifera were char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Pritchard et al (2010) compared the use of aluminum sulfate and powder obtained from MO seeds separately on purification of drinking water and showed that MO removed 84% turbidity and 88% E. coli, whereas alum removed greater than 99% turbidity and E. coli. Few studies focus on using a combination of MO and other coagulants such as arabic gum (Alang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Pritchard et al (2010) compared the use of aluminum sulfate and powder obtained from MO seeds separately on purification of drinking water and showed that MO removed 84% turbidity and 88% E. coli, whereas alum removed greater than 99% turbidity and E. coli. Few studies focus on using a combination of MO and other coagulants such as arabic gum (Alang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moringa bark gum (MOG) is reported to have gel forming potential for topical preparations 10 as well as the graft copolymer of MOG grafted with polyacrylamide (PAAM) along with the blends of Gum Ghatti are utilized as efficient flocculant systems for sewage cleaning. 11 Moreover, biodegradation is a major issue with various synthetic polymers. Thus, various natural polymers are combined with synthetic polymers to make them biodegradable 12 and thus as an evidence for bacterial biodegradation, the polymers are tested in presence of bacterial culture, as these polymers degrades in presence of bacterial enzymes and thereby render them to be environment friendly.…”
Section: Introductionmentioning
confidence: 99%